Couple communication and contraception use in urban Senegal. (June 2021) - Grabert, Brigid K; Speizer, Ilene S; Domino, Marisa Elena; Frerichs, Leah; Corneli, Amy; Fried, Bruce J
Objectives: Couple communication about family planning has been shown to increase uptake of contraception. However, couple communication is often measured based solely on one partner's report of communication. This research investigates the influence of couple-reported communication about family planning on current and future use of contraception using couple-level data. Methods: We used baseline data from the Measurement, Learning, and Evaluation (MLE) project collected through household surveys in 2011 from a cross-sectional representative sample of women and men in urban Senegal to conduct secondary data analysis. We used multivariable logit models to estimate the average marginal effects of couple communication about family planning on current contraception use and future intention to use contraception. Results: Couple communication about family planning reported by both partners was significantly associated with an increased likelihood of current use of contraception and with future intention to use contraception among non-contracepting couples. Couples where one partner reported discussing family planning had a 25% point greater likelihood of current contraception use than couples where neither partner reported discussing, while couples where both partners reported discussing family planning had a 56% point greater likelihood of current contraception use, representing more than twice the effect size. Among couples not using contraception, couples where one partner reported discussing family planning had a 15% point greater likelihood of future intention to use contraception than couples where neither partner reported discussing, while couples where both partners reported discussing family planning had a 38% point greater likelihood of future intention to use contraception. Conclusion: These findings underscore the importance of the inclusion of both partners in family planning programs to increase communication about contraception and highlight the need for future research using couple-level data, measures, and analysis.